Caring at the transition: success and financial barriers of fidaxomicin discharge prescriptions for inpatients with Clostridioides difficile infection - Ellen Earle; Jigar Mehta; Alexis Blecher; Matthew Shou Lun Lee (Antimicrobial Stewardship & Healthcare Epidemiology)
This retrospective cohort study evaluated the proportion of inpatients initiated and successfully discharged on fidaxomicin for Clostridioides difficile infection. Nearly, all patients (96.4%; 27/28) were able to obtain fidaxomicin to complete their treatment course, although there was variability in copays among patients with Medicare.